COVID-19 and its reflection on SMEs in developing countries - Tambunan, Tulus, 1956-; Himachalam, D. (Small business considerations, economics and research (Series), 2022)
"This book contains empirical analysis of the impact of the COVID-19 pandemic crisis on micro, small, and medium enterprises (MSMEs) in a number of developing countries including Indonesia, India, Sri Lanka, Vietnam, Brunei Darussalam and South Africa. This book also provides an explanation of the theory of transformation channels through which the pandemic crisis has affected MSMEs"--